1974
DOI: 10.1037/h0036930
|View full text |Cite
|
Sign up to set email alerts
|

Training for thematic-fantasy play in culturally disadvantaged children: Preliminary results.

Abstract: Disadvantaged preschool children directed in the role-enactment of imaginary stories were found to be superior to control children (who did not engage in role playing) on several measures of social and cognitive development. Fantasy play training resulted in a higher incidence of spontaneous sociodramatic play, higher scores on an interpersonal perception test, and better performance on tasks measuring story sequential memory and story verbalization skills. However, this training did not improve performance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 8 publications
3
59
1
Order By: Relevance
“…Saltz and Johnson (1974) found improvement in affective perspective taking following thematic fantasy training (acting out stories) but not following training in identifying object dimensions or no training at all. However, Saltz's second study (Saltz et al, 1977) showed no main effect of thematic fantasy or sociodramatic play, yet they went on to compare thematic fantasy only with the other three groups combined (sociodramatic play, fantasy discussion, and control), and only for the first two years of the 3-year study-not accepted statistical practice.…”
Section: Social Pretensementioning
confidence: 88%
“…Saltz and Johnson (1974) found improvement in affective perspective taking following thematic fantasy training (acting out stories) but not following training in identifying object dimensions or no training at all. However, Saltz's second study (Saltz et al, 1977) showed no main effect of thematic fantasy or sociodramatic play, yet they went on to compare thematic fantasy only with the other three groups combined (sociodramatic play, fantasy discussion, and control), and only for the first two years of the 3-year study-not accepted statistical practice.…”
Section: Social Pretensementioning
confidence: 88%
“…Similarly, Tamburini (1982) provides evidence that careful adult guidance and suggestion can enhance the quality and inventiveness of play. Moreover, Saltz and his colleagues (Saltz & Johnson, 1974;Saltz et al, 1977;Saltz & Brodie, 1982) have been most concerned with the tutorial benefits of dramatic play.…”
Section: When Children Have Difficulty Playing With Other Children 3mentioning
confidence: 98%
“…For example, Marshall & Hahn (1967) used adults who presented dramatic situations and plots; 58 ELENIMELLOU Freyberg (1973) also used pipe cleaner figures acting roles which the children then took over, using toys as props; Saltz & Johnson (1974) used thematic dramatic play; Feitelson & Ross (1973), Fink (1976), Smith & Syddall (1978), Smith et al (1981), Christie (1983) and Udwin (1983) used play tutoring; and Smilansky (1968) used a combination of play tutoring and excursions. The benefits from the interventions include originality, fluency, flexibility, complexity of play, concentration, conservation of social role, verbalization, group constructs and cooperation, perceptual, cognitive and affective tasks, improved understanding of conservation of mass and liquid and also mathematical readiness.…”
Section: When Children Have Difficulty Playing With Other Children 3mentioning
confidence: 99%
“…Indeed, the terms 'imaginative play 1 (e.g., Shmukler, 1981Shmukler, ,1983Udwin, 1983;Moran et ul, 1984); 'make-believe' (e.g., Singer, 1973;Singer & Singer, 1976Bretherton, 1989); 'fantasy play 1 (e.g., Cole & LaVbie, 1985;Forbes et ul, 1986;Olszewski, 1987;Wall et ul, 1989); 'symbolic play' (e.g., Chaille, 1977;Christie, 1986;Hughes, 1987;Nourot & Van Hoorn, 1991); and 'sociodramatic play' (e.g., Christie, 1982;Klugman & Smilansky, 1990;Shefatya, 1990;Smilansky & Shefatya, 1990), have been frequently used as having the same meaning. Saltz & Johnson (1974), on the one hand use as akin 'sociodramatic' and 'dramatic' play, and on the other hand they distinguish TFP (thematic-fantasy play), that is their own use of this term, from sociodramatic play. This type of play (TFP), they write, is similar to sociodramatic play in that it involves verbal role enactment in a group, but on the other hand unlike sociodramatic play, TFP employs a structured play theme or story plot.…”
Section: Various Definitions Of Pretence Characteristicsmentioning
confidence: 98%